2018
DOI: 10.1021/acs.inorgchem.8b02474
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Structural Studies on the Ln(III)/An(III) Malate Complexation

Abstract: The complexation of the trivalent lanthanides Nd­(III) and Eu­(III) and of the actinide Am­(III) with malate was studied using a multi-method approach. The combination of structural and thermodynamic studies was required for the interpretation of the stoichiometry and thermodynamic data (log β0, Δr H 0 m, Δr S 0 m, Δr G 0 m) of the lanthanide/actinide malate complexes leading to a profound molecular understanding of the system. The structure-sensitive methods vibrational spectroscopy and extended X-ray absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 83 publications
3
9
0
Order By: Relevance
“…In Section , it was shown that the highest complexation order is two for Mala and Mal and one for the other ligands. These results indicate that Mala binds to Am­(III) via a tridentate binding mode, as also suggested by Taube et al based on IR and EXAFS results . A bidentate binding mode is suggested for the other dicarboxylate and acetate ligands.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…In Section , it was shown that the highest complexation order is two for Mala and Mal and one for the other ligands. These results indicate that Mala binds to Am­(III) via a tridentate binding mode, as also suggested by Taube et al based on IR and EXAFS results . A bidentate binding mode is suggested for the other dicarboxylate and acetate ligands.…”
Section: Resultssupporting
confidence: 84%
“…These spectroscopic data consistently indicate side-on bidentate binding of a Mal ligand; each of the two carboxylate groups in a Mal ligand binds to an Am­(III) ion via a monodentate binding mode, resulting in a 6-membered ring structure formation, as depicted in Figure (b). The same changes were observed in the IR absorption spectra of the Mala ligand (Figure (b)), which were reported to form a tridentate chelating structure with two carboxylates and a hydroxyl group bound to a Nd­(III) ion . This similarity between the Mal and Mala complexes further supports a side-on binding of the Mal.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The black oxide was related with incorporation of carbon-bearing elements, such as carbonates, carboxylates, carbonyls of aluminum, or amorphous carbon into the AAO walls [21,41,42]. The violet-blue-green colouration of AAO fabricated in malic acid may indicate the incorporation of Al(III)-malic acid complexes into the AAO framework, since some metal-malate complexes demonstrate the absorption in the visible part of the spectrum [43,44]. 6.…”
Section: Resultsmentioning
confidence: 99%